Ways of Efficient Use of Water in the Agricultural Sector According to the Practice of Official Statistics of the Countries of the World - V. PANTELEIEV; O. KHARLAMOV (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
Multi-sectoral and rational use of water resources for the needs of agriculture, the availability of capital-intensive hydrotechnical infrastructure in view of its technical condition and the possibility of regulating the water regime, the need to take into account the requirements of environmental protection (first of all, the inadmissibility of the deterioration of the ecological characteristics of reclaimed land), as well as the need to ensure economic efficiency from investment funds actualize the application of an integrated approach to the management of agricultural production on reclaimed land. The results of statistical studies become a strong foundation for the justification of state regulation and management decision-making. Under such conditions, the scenario of using methods and tools of official statistics in the practice of water management is optimal. In Ukraine, the reform of the state management system regarding irrigation and drainage for the needs of the agricultural sector, which was reflected in the «Strategy of Irrigation and Drainage in Ukraine for the period until 2030» [1], is gaining importance. There is a need to use the formed historical statistical information on the management of water resources on irrigated lands for the cultivation of agricultural crops. To strengthen the significance of statistics, it is necessary to use its data when studying the dynamics of the share of irrigation water use in the total amount of fresh water used in Ukraine. The status of a water user as an active agent of agricultural production processes in the conditions of implementation of irrigation measures requires the provision of appropriate statistical reports on the use of withdrawn water for certain needs. The data on water use reflected in the reports form the basis of decision-making and evaluation of their effectiveness. Due to the need for the implementation of international and European norms and standards in the field of environmental statistics and multi-sectoral statistics, there is a need to consider the world experience of applying both statistical methods of water resources research in countries with a market economy, as well as the main provisions of recommendations on water resources statistics, proposals and examples of decision-making using statistical data, data elements regarding water resources of Ukraine. Based on these starting points, the article systematizes the methodical techniques of water resources research statistics, formulates the chain of management and reporting on water resources based on the ecological and economic accounting by the water user, reveals the necessary changes in the regulatory support for the preparation of statistical reporting according to the rules of ecological and economic accounting, formulates conclusions from conducted research and outlined directions for further research.  The main sources of information in the article are data from the State Statistics Service of Ukraine, regulatory and legal acts of Ukraine, the UN, EU and World Bank bodies, data from scientific studies on the application of statistical methods in the effective use of water on reclaimed lands for the period 1991–2023, administrative data.